The Dating of the Acta Carpi - Kozlowski, Jan M. (Vigiliae Christianae, 2021)
Abstract In the scholarly discussion on the dating of the Acta Carpi , two main proposals were hitherto formed: either II or III c. CE . The article argues that the earlier dating is probable. The Acta Carpi show many parallels with the Martyrium Polycarpi which can be best explained by a direct relationship between the two texts. Since the Acta Carpi betray more archaic features than the Martyrium Polycarpi , which in light of recent studies should be dated to the end of the second century, it is inferred that the Acta Carpi were written in the II c. CE , most probably in the years 166–168.